Comment piece: The inspection of Offender Management in Custody – new resettlement policy, same old problems - Cracknell, Matthew (Probation journal, 2023)
Two inspection reports regarding the latest resettlement policy – Offender Management in Custody – have recently been published (HM Probation Inspectorate and HM Prison Inspectorate, 2022; HM Inspectorate of Probation, 2023). This comment piece provides a brief analysis of these inspection reports, which demonstrates how Offender Management in Custody is undermined by five issues: a fixed and fragmented model of delivery; poor identification of needs and service provision; poor quality keywork; understaffing in prisons and probation; and finally, poor communication between prison and probation practitioners. This comment piece then places these failures into context, asserting that there has been a longstanding ‘common thread’ of issues that has undermined past resettlement policies and that these have permeated through to Offender Management in Custody. This commentary concludes by suggesting a possible way forward with the Offender Management in Custody model, noting that no resettlement policy will be successful unless the staffing crisis in prisons and probation is resolved, and the practitioners responsible for Offender Management in Custody are provided with sufficient time and resources to provide quality resettlement support.